Shared decision making about pain management in labour: expectations and reality. (16th November 2010) - Lally, JE; Thomson, R; Exley, C; Macphail, S
Abstract : Introduction: Pregnant women expect to be involved in decisions about their care with clinicians, sharing information, knowledge and experience, in order to make decisions together. Shared decision making is especially pertinent in management of pain in labour where there are many options available, with varying degrees of evidence and acceptability. Objective: To better understand the current decision making process and expectations and experience regarding pain relief in labour. To understand from both pregnant women's and the professionals' perspectives how this could be improved. Methods: Semistructured interviews with women at various stages of pregnancy and focus groups with obstetricians, anaesthetists, delivery suite and community midwives. Data analysed using the constant comparison method. Results: There was agreement among professionals that women were generally unprepared for labour. Women reported accessing many different sources of information but still felt largely unprepared. There was discordance between what the professionals said they told women and the information women wanted. There was also little evidence that women's values were elicited to help them choose pain relief that matched their preferences and values for example, if midwives knew women valued mobility, it is clear an epidural wouldn't be congruent with her values and this mismatching would need to be discussed with the woman. Conclusion: Work needs to be undertaken in the form of decision support with both women and professionals to ensure that women are adequately prepared in order to engage in the decision making process, to ensure that shared decision making is a reality and not an aspiration.